The resource handbook for academic deans - Behling, Laura L., 1967-; American Conference of Academic Deans (San Francisco : Jossey-Bass, a Wiley Brand, 2014)
'From the American Conference of Academic Deans comes the third edition of the handbook written for and by academic deans. Since the publication of the second edition, higher education has changed significantly and as a result, so has the role of the dean. This new edition addresses the work of a dean, from building a relationship with the president to deciding when to leave an institution. Many of the changes to the Handbook are based on input and surveys from ACAD members about what issues are most important to them.'--
'Sponsored by the American Conference of Academic Deans (ACAD).'
Includes bibliographical references and index.
Keywords: Universities and colleges -- United States -- Administration; Deans (Education) -- United States